PERAN KELUARGA DAN WARGA SEKITAR DALAM PENCEGAHAN TUBERCULOSIS - Develsio, Marco; Manona, Sharon; Yoan, Nindita; Hijriah, Novita; Ramatillah, Diana; Dyanto, Norman (BERDIKARI, 2025)
Tuberculosis (TB) is a chronic infectious disease that remains a global health problem. Indonesia ranks second in the world after India in terms of TB cases. Preventing TB transmission requires not only medical intervention but also family and community support. Effective education can increase public understanding and awareness of TB. The purpose of this study was to determine the effectiveness of health education in increasing public knowledge about TB prevention. This study used a pre-test and post-test design without a control group. The education was conducted in RT 08/RW 07, Sunter, North Jakarta, involving 32 participants. Data were collected through 10 pre-test and post-test questions related to knowledge about TB. The results were analyzed using the average percentage of correct answers before and after the education. The pre-test results showed that the average knowledge of the community was 78.5%, while the post-test results increased to 100%. This increase shows that health education is effective in improving community knowledge about TB prevention and treatment. Health education has been proven to significantly increase community knowledge.